Diphtheria: A Case Series From Central India - Swati, Gajbhiye; Sundaram, Supare; Geetika, Agrawal; Sandeep, Kokate; Sunita, Gajbhiye (Journal of Neonatal Surgery, 2025)
Background: Diphtheria continues to be a public health problem in India as it is re-emerging in several regions of the country. In recent times, apart from preschool-aged children, diphtheria outbreaks are seen to affect older children and adults. Recent emergence of cases highlights the risk diphtheria poses when civil unrest interrupts vaccination and healthcare access. An improved understanding of the nature of each outbreak is therefore essential to generate a pool of evidence regarding the current disease status in India. Here we describe the case series of diphtheria from Central part of India so as to better understand the natural history of disease, key epidemiological factors, the role of asymptomatic carriers in transmission and effectiveness of control measures so as to improve clinical practices and support alternative strategies for response to future diphtheria outbreaks. Results: Among the 10 patients admitted with clinical suspicion of oropharyngeal diphtheria. Microbiological diagnosis was achieved in 3 cases and one was diagnosed clinically. All the 3 bacteriological positive cases were of pediatric age group with incomplete immunization. All the positive cases were found to be originated from inmates of boarding school inhabiting the same residential area. Of the 10 patients, eight (80%) recovered, one (10%) succumbed to death while one took discharge against medical advice. Clinical presentations, vaccination history and microbiologic findings points towards the persistence of toxigenic strain of C. diphtheriae (gravis type) along with other rare corynebacterium spp. that clinically mimic as oropharyngeal diphtheria in the community and their role in disease transmission with potential for future outbreaks. Conclusion: Awareness among people, widespread universal immunization coverage especially in cohorts of children, availability of modern microbiological support, and rapid early diagnosis are the cardinal steps to control diphtheria resurgence.